Typology of households adopting improved soybean technology: an application of the discriminant analysis model in northern Nigeria - Ojiako, I.A.; Manyong, Victor M.; Ikpi, A. (2008)
A two-stage typology of adopters and non-adopters of improved soybean varieties introduced to farmers in northern Nigeria was investigated using the discriminant analysis model. Labour expenses, active membership of associations and exposure to extension services significantly discriminated the two groups, out of thirteen factors used in the linear discriminating Junction. Involved alone in a second-stage of model discrimination, the three variables achieved a 94.1 percent correct classification performance. The linear discriminating Junctions' coefficients were positive for the three variables, implying that the chances of belonging to the high adoption group would increase if these characteristics increased in magnitude. In scaling out crop-improvement technologies to households attention should be focused an these institutional and financial factors that best facilitated adoption of new crop germplasm.